2019
DOI: 10.1111/grs.12234
|View full text |Cite
|
Sign up to set email alerts
|

Effects of calcium application on the salt tolerance and sodium excretion from salt glands in zoysiagrass (Zoysia japonica)

Abstract: Zoysiagrass (Zoysia japonica Steud.), a native grass in Japan, is a warm‐season turfgrass displaying high salt tolerance, mainly derived from salt excretion through salt glands. The present study focused on how external calcium (Ca) affects sodium (Na) excretion from salt glands to relieve salt stress, including response to oxidative stress, and discussed the physiological mechanisms possibly involved. Treatments using 0, 25, 50, 75, 100, 125 and 150 mmol/L sodium chloride (NaCl), with or without applying 2 or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…The result indicated that there were increment in CAT, POD enzymes activity and proline content, in each two cultivars in the control treatment and this agreed with Zhang et al (2013), Hela et al (2011 and Younis et al (2008) that high salt led to increase in CAT and Zhang et al (2013), Hela et al (2011 and Younis et al (2008) that high salt led to increase in CAT and POD enzymes and proline supplement of sulfur led to increase the metabolism of Thiobacillus thioparus bacteria and led to the pH lower and increasing the availability of macro and micro nutrients which lead to increase the solutes which adjusting the water potential and finally regulate the cellular water and absorption of water by plant (Abdelhamid et al, 2013;Kadhim, 2016;Riffat & Ahmad, 2018) and finally reduce CAT, POD and proline. Addition of calicium act on increasing the synthesize of carbohydrates and various solutes that lead to adjusting cellular potential (Tian et al, 2015) and this agreed with Maeda (2019) that the use of calcium act to promote growth and decrease proline and CAT, POD enzymes.This result indicate that sulfur and clean salt ameliorates the adverse effects of salinity on lettuce plants that grow on sodic soil.…”
Section: Resultssupporting
confidence: 65%
“…The result indicated that there were increment in CAT, POD enzymes activity and proline content, in each two cultivars in the control treatment and this agreed with Zhang et al (2013), Hela et al (2011 and Younis et al (2008) that high salt led to increase in CAT and Zhang et al (2013), Hela et al (2011 and Younis et al (2008) that high salt led to increase in CAT and POD enzymes and proline supplement of sulfur led to increase the metabolism of Thiobacillus thioparus bacteria and led to the pH lower and increasing the availability of macro and micro nutrients which lead to increase the solutes which adjusting the water potential and finally regulate the cellular water and absorption of water by plant (Abdelhamid et al, 2013;Kadhim, 2016;Riffat & Ahmad, 2018) and finally reduce CAT, POD and proline. Addition of calicium act on increasing the synthesize of carbohydrates and various solutes that lead to adjusting cellular potential (Tian et al, 2015) and this agreed with Maeda (2019) that the use of calcium act to promote growth and decrease proline and CAT, POD enzymes.This result indicate that sulfur and clean salt ameliorates the adverse effects of salinity on lettuce plants that grow on sodic soil.…”
Section: Resultssupporting
confidence: 65%
“…It was shown that Ca 2+ promotes the secretion of Na + from salt glands of recretohalophytes ( Ding et al., 2010 ; Maeda, 2019 ). In our previous study on whole-leaf secretion rates in P. auriculata under salt stress, Ca 2+ content in diploid leaves was higher than that in tetraploid leaves, but the Na + secretion rate was lower in diploids than in tetraploids ( Duan et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mg 2+ is a key component of plant chlorophyll and has antiaging function (Khan et al., 1999). The high concentration of Na + has high activity of replacing Ca 2+ from the plasma membrane, and the balance of Ca 2+ in the cell is affected (Maeda, 2019). The imbalance of intracellular Ca 2+ is the primary response to salt stress, which leads to many secondary salt damage reactions (Storey, 1995).…”
Section: Discussionmentioning
confidence: 99%